Analysis of Drought Disaster Potential Based on Remote Sensing and Geographic Information Systems (Case Study: North Central Timor Regency) - Ware, Yohanes; Somantri, lili (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
Drought is a natural phenomenon that is a complex and difficult to predict and has the potential to be detrimental to human life, so mitigation efforts need to be made to reduce its impact. To provide information related to drought in North Central Timor District, it is necessary to make efforts to map areas that are vulnerable to drought. Mapping drought potential can be done by utilizing remote sensing data and using Geographic Information Systems (GIS). The aim of this study is to determine the distribution of drought potential in TTU Regency using remote sensing and GIS. The method used is the scoring and overlay method using ArcMap by paying attention to several parameters, such as rainfall, slope, type of soil, and land use. The results of the analysis show that the level of drought in the TTU regency is in the medium to high category, so it is necessary to mitigate drought efforts. Overlay analysis identified low drought class reaching 1,8 km2 or 0,1%, medium drought with an area of 1696,1 km2 or 65,4%, high drought class covering an area of 894,9 km2 or 35%, and very high drought class covering 0,08 km2 or 0,01% of TTU Regency area.